Mexican Sunflower (Tithonia diversifolia) as a Source of Organic Matter in Potato Cultivation - F. Deru Dewanti; Yonny Koetjoro; Didik Utomo Pribadi (Nusantara Science and Technology Proceedings)
One of the low production of potatoes is the lack of land carrying capacity. The availability of nutrients greatly affects the growth and yield of plants. During this time excessive and continuous use of inorganic fertilizers can lead to a decrease in soil fertility rates. Paitan plants have only been used as a fence plant and still not widely used as a producer of organic nutrients, especially in potatoes. Utilization of mexican sunflower as a supplier of organic materials can be done easily and efficiently because mexican sunflower plants are very easy to get and grown widely. This plants are widespread in the region of East Java. The purpose of this research is to obtain the potential of paitan as a supplier of organic materials to increase growth and yield of granola potato optimum. This study used experimental method with Randomized Group Design (RGD). Treatment using mexican sunflower dose (D) consists of: D0 = Control, without fertilization, D1 = 120 kg N/ha equivalent to fresh mexican sunflower 5.882 ton/ha, D2 = 175 kg N/ha equivalent to fresh mexican sunflower 8.578 ton/ha, D3 = 230 kg N/ha equivalent to fresh mexican sunflower 11,273 ton/ha, D4 = 175 kg N/ha Urea equivalent to 380 kg/ha, P2O 149.76 kg/ha, K2O 100 kg/ha. The results of the study obtained mexican sunflower with a dose of fertilization 11,273 ton/ha equivalent to 230 kg N/ha (D3) can produce growth and yield of the highest potato crops. Mexican sunflower as an organic fertilizer can improve soil fertility and be able to provide nutrients to plants.